Implementasi Kebijakan Peraturan Presiden Nomor 112 Tahun 2007 Tentang Penataan Dan Pembinaan Pasar Tradisional Pusat Pembelanjaan Dan Toko Modern Dalam Meningkatkan Tingkat Ketertiban Di Pasar Pelita Kota Sukabumi - Jaelani, Ijan; Rachmawati, Ike (Peneliti.net, 2024)
The presence of modern markets can be considered by various groups to have cornered the existence of traditional markets. Presidential Regulation Number 112 of 2007 concerning the Arrangement and Development of Traditional Markets, Shopping Centers and Modern Stores is expected to be implemented with the aim of facilitating public order in the implementation of every form of business. Pelita Market, Sukabumi City, in its arrangement and order in the field, has established good communication, although it is not very optimal because as time goes by traders begin to ignore the public order policy. In terms of human resources, they are competent and adequate, but there is still a lack of financial resources. The disposition of an implementor is said to be good because it has the main capital needed by the implementor in the market environment. Good and structured coordination and cooperation between all parties in the organizational structure.